THE IMPACT OF GREEN BUSINESS EDUCATION AMONG ENTREPRENEURS ON THE ECONOMY: A LITERATURE REVIEW (Marketing Journal, 2025)
This literature review examines how educating entrepreneurs in “green business” principles influences economic outcomes. We conducted a structured review of high - impact academic articles linking sustainability -focused entrepreneurship education with indica tors such as employment, innovation, and GDP growth. The findings indicate that entrepreneurship education oriented to environmental sustainability increases entrepreneurs’ intention and ability to create eco -friendly ventures. Such green startups tend to create jobs, drive inclusive growth and innovation, and do so with reduced ecological harm compared to traditional businesses. These insights underscore the importance of integrating sustainability into entrepreneurship curricula. Policymakers and educator s should support green entrepreneurship training to foster sustainable economic development. This review synthesizes cross -disciplinary global evidence that green business education can advance economic prosperity alongside environmental stewardship.
Keywords: green business education; entrepreneurship education; sustainable entrepreneurship; economic development; innovation; inclusive growth; environmental sustainability